(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The development of malignant tumor diseases of the blood system is associated with the occurrence of a number of successive gene mutations leading to the development of a malignant cell clone. It is also known that during therapy, the primary population of malignant cells can acquire secondary mutations, changing under the influence of various selection factors in the patient’s body (immunological selection, the action of cytostatic drugs, etc.)